Better Governance for Biodiversity Conservation is Possible in Romania? - Florentina, Gheorghe Iuliana; Maria, Cocioaba Suzana; Adrian, Lorent; Simona, Mihailescu (Journal of Environmental Science and Engineering Technology, 2015)
Romania is one of the countries with a long tradition in biodiversity conservation. Regulations on nature protection included in Romanian law were first signaled in the 15th century. Although in the inter-bellum and communist periods the regulations were relatively fewer and the inflexible legislative framework had no focus on conservation, biodiversity and natural capital conservation happened by itself. After 1989, although there have been numerous legislative amendments and an opening concerning the signing of international conventions, the transposition of European biodiversity conservation legislation and support of large amounts of money; the efficiency of conservation is increasingly weaker. The Convention on Biodiversity (CBD), signed by Romania in 1992 was ratified by European Union in 1993. Since 2007 Romania, as an EU state member, must comply with commitments to the Convention in both positions. Natura 2000 network of protected areas is the key legal instrument in applying the sustainability principles to biodiversity. In order to ensure that the existing biodiversity is maintained, Romania has developed three National Strategies and an action Plan for Biodiversity Conservation. In all three, Romanian experts settled: the priority objectives, the priority areas for nature and biodiversity conservation, the ways of reforming the legal and institutional framework; the cost estimate to achieve the major objectives. The estimated budget necessary to implement the action plan is about 1,508,175,000 € out of which a small portion was spent, with very low efficiency.